Aging in the 1980s: Psychological Issues. 1980
DOI: 10.1037/10050-012
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic drug effects on memory and cognition in humans.

Abstract: This chapter summarizes recent attempts to improve normal memory functioning and to alleviate age-related memory deficits by administering drugs that affect transmission at cholinergic synapses. In young adults, a low dose of physostigmine, a short-acting cholinesterase inhibitor, enhanced storage of in formation in long-term memory. Higher doses of physostigmine impaired all aspects of memory. Choline chloride, a precursor to acetylcholine, did not have a substantial effect on memory in a series of four studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Starting at 15 minutes into the infusion and ending approximately five minutes after the end of the infusion, patients were given three trials on a visual recognition memory task. This task measures a patient's ability to store and retrieve information in long‐term memory, an ability that is known to be severely impaired in patients with AD/SDAT 27 and an ability that is known to be sensitive to fluctuations in cholinergic activity 28 . On trial each patient was first shown 12 words or pictures one at a time, then the 12 studied items were randomly mixed together with 12 similar words or pictures that had not been presented to the patient previously.…”
Section: Methodsmentioning
confidence: 99%
“…Starting at 15 minutes into the infusion and ending approximately five minutes after the end of the infusion, patients were given three trials on a visual recognition memory task. This task measures a patient's ability to store and retrieve information in long‐term memory, an ability that is known to be severely impaired in patients with AD/SDAT 27 and an ability that is known to be sensitive to fluctuations in cholinergic activity 28 . On trial each patient was first shown 12 words or pictures one at a time, then the 12 studied items were randomly mixed together with 12 similar words or pictures that had not been presented to the patient previously.…”
Section: Methodsmentioning
confidence: 99%
“…19 The work done with cholinergic/anticholinergic drugs supports the important role of cholinergic response in age-related memory impairments and in research in other neurotransmitter systems. Their effects on psychological performance or observed changes depend on a variety of factors, including the drug used, the dose of the drug, the subjects, and the psychological assessment procedures used."…”
Section: Treatmentmentioning
confidence: 97%
“…14 Arecoline, another cholinergic agonist, was found to improve learning in an inverse relationship to baseline memory performance. 19 A study in which arecoline was combined with physostigmine resulted in identical effects in both presenile Alzheimer's patients and normal patients." The ability of physostigmine and arecoline to improve performance is tempered by the adverse side effects, short half-life, and narrow effective dose range."…”
Section: Treatmentmentioning
confidence: 98%
See 2 more Smart Citations